ChemInform Abstract: A Journey into Recent Microwave‐Assisted Carbohydrate Chemistry. Issue 32 (18th July 2013) - Corsaro, Antonino; Pistara, Venerando; Chiacchio, Maria Assunta; Romeo, Giovanni
Abstract Review: 131 refs.